1980
DOI: 10.1126/science.207.4429.446
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Structure of the Ionosphere and Upper Neutral Atmosphere of Saturn from the Pioneer Radio Occultation

Abstract: Radio occultation measurements at S band (2.293 gigahertz) of the ionosphere and upper neutral atmosphere of Saturn were obtained during the flyby of the Pioneer 11 Saturn spacecraft on 5 September 1979. Preliminary analysis of the occultation exit data taken at a latitude of 9.5 degrees S and a solar zenith angle of 90.6 degrees revealed the presence of a rather thin ionosphere, having a main peak electron density of about 9.4 x 10/(3) per cubic centimeter at an altitude of about 2800 above the level of a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 9 publications
2
20
1
Order By: Relevance
“…Prior to the Grand Finale, the final phase of the Cassini mission, no in situ measurements of the Kronian ionosphere had been made. Properties of Saturn's ionosphere were inferred based on three different remote observation methods: radio occultation (Kliore et al, , , ; Nagy et al, ), radio emission from Saturn electrostatic discharges (Fischer et al, ; Kaiser et al, ), and millimeter‐band observations of protonated molecular hydrogen ( normalH3+; O'Donoghue et al, ). However, only the radio occultation technique has yielded the altitude structure of the electron density.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the Grand Finale, the final phase of the Cassini mission, no in situ measurements of the Kronian ionosphere had been made. Properties of Saturn's ionosphere were inferred based on three different remote observation methods: radio occultation (Kliore et al, , , ; Nagy et al, ), radio emission from Saturn electrostatic discharges (Fischer et al, ; Kaiser et al, ), and millimeter‐band observations of protonated molecular hydrogen ( normalH3+; O'Donoghue et al, ). However, only the radio occultation technique has yielded the altitude structure of the electron density.…”
Section: Introductionmentioning
confidence: 99%
“…Early Saturn 31 ionospheric models (e.g., McElroy, 1973;Capone et al, 1977) predicted electron densities an 32 order of magnitude larger than those later measured by the Pioneer 11 and Voyager spacecraft 33 (Kliore et al, 1980;Kaiser et al, 1984;Lindal et al, 1985). One chemical effect of introducing 34 oxygen bearing compounds into Saturn's upper atmosphere is to convert H + -a long-lived major 35 atomic ion in outer planet ionospheres -into a short-lived molecular ion that quickly 36 dissociatively recombines, thereby reducing the net electron density.…”
Section: Water In Saturn's Ionosphere 29mentioning
confidence: 99%
“…Fig. 2 shows the deduced ionospheric n e profiles for Saturn from the Pioneer 11 (Kliore et al, 1980) and Voyager 1 and 2 (Lindal et al, 1985) RSS experiments. The Pioneer data revealed multiple n e (Lindal et al, 1987) and Neptune (Lindal, 1992) have been observed by the Voyager 2 radio occultation experiments.…”
Section: Observed Ionospheric Structurementioning
confidence: 99%